Menumbuhkan Sebuah Kepribadi Kreatif dengan Dorongan Motivasi di Panti Asuhan Yayasan Nischaya Indonesia - Farah Adzraa Isty; Randa Putra Kasea Sinaga (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2023)
Creativity is an ability to create something new, to provide creative ideas in solving problems or an ability to see new relationships between elements that previously existed. Because creativity is the result of a person's creative thinking process, creative thinking is closely related to creativity. Creativity is also the skill of determining new ideas by looking at the subject from a new perspective and forming new combinations of two or more concepts in mind. Children’s orphanage is a social welfare business institution that has a special responsibility. His responsibility is to provide social welfare services to neglected children by carrying out sponsorship and alleviation of neglected children. This place also provides substitute parent/guardian services in meeting the physical, mental and social needs of foster children. Therefore, children here can still get broad, appropriate and adequate opportunities for the development of their personality. With the existence of motivation is an internal and external encouragement within a person which is indicated by the desire and interest, encouragement and needs, hopes and aspirations, appreciation, and respect. In Field Work Practice II this time it was carried out using the groupwork method through the general or general intervention phase which consisted of Engagement Intake Contract, Assessment, Planning/Planning, Intervention, Evaluation, and Termination. The focus of the client's problem solving process is to make fun activities that can generate creativity in clients. It is hoped that after doing practicum at the orphanage the children are expected to be able to understand and understand that creativity is important in life, especially in early childhood because it can make children more productive.